Repair methods of river channel ecological landscape. (October 2018) - Sun, Shuai; Wang, Biao
Abstract: Fluvial greenway connectivity has multiple dimensions, so it is the complex ecosystems of nature. The longitudinal connectivity of fluvial greenway is directly related to the natural flow of water, and is sensible and cognizable. The lateral Connectivity of fluvial greenway is closely linked to the Flood Pulse Concept and river cross-section design. The vertical connectivity of fluvial greenway refers to the vertical materials and energy circulation performance and the biocoenosis relevancy in the cross section of the river. They constitute the complicated continuum system of fluvial greenway.